Hubungan Kecerdasan Emosional Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Di SD Negeri 104333 Marubun Tahun Ajaran 2021/2022 - Eti Muliani; Juwita Tindaon (JURNAL HANDAYANI PGSD FIP UNIMED, 2022)
Abstract: Relationship of Emotional Intelligence to Student Learning Outcomes in Social Studies Subjects at State Elementary School 104333 Marubun Academic Year 2021/2022, This research was carried out at the State Elementary School 104333 Marubun, the sample in this study was class V students, totaling 30 students. The purpose of this study was to determine whether the relationship between emotional intelligence and student learning outcomes in social studies subjects at the State Elementary School 104333 Marubun for the Academic Year 2021/2022. The type of research carried out is quasi-experimental, namely research that aims to determine emotional intelligence with social studies learning outcomes for fifth grade students. Data analysis used the Product Moment Correlation formula. Based on the data analysis, it was obtained that the description of emotional intelligence at the State Elementary School 104333 Marubun was in the fairly good category, because from the average score of the questionnaire, the score was 59.60 and included in the fairly good category. While the Social Studies learning outcomes of Class V State Elementary School 104333 Marubun are in the good category, because the value of student learning outcomes is 75.93 and is in the good category. For the correlation test, the t value is 4.942 while the t in the table is 2.05 so that the t count is greater than t in the table, so there is a significant relationship between emotional intelligence and social studies learning outcomes for fifth grade students at State Elementary School 104333 Marubun Academic Year 2021/ 2022.Keywords: : Giving Reinforcement and Civics Learning OutcomesAbstrak: Hubungan Kecerdasan Emosional Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Di SD Negeri 104333 Marubun Tahun Ajaran 2021/2022, penelitian ini dilaksanakan di SD Negeri 104333 Marubun, yang menjadi sampel dalam penelitian ini adalah siswa kelas V yang berjumlah 30 orang siswa. Adapun tujuan dalam penelitian ini adalah untuk mengetahui apakah hubungan kecerdasan emosional terhadap hasil belajar siswa pada mata pelajaran IPS di SD Negeri 104333 Marubun Tahun Ajaran 2021/2022. Jenis penelitian yang dilakukan adalah quasi eksperimen, yaitu penelitian yang bertujuan untuk mengetahui kecerdasan emosional dengan hasil belajar IPS siswa kelas V. Analisis data yang digunakan menggunakan rumus Kolerasi Product Moment. Berdasarkan analisis data diperoleh gambaran kecerdasan emosional di SD Negeri 104333 Marubun masuk dalam kategori cukup baik, karena dari nilai rata-rata angket diperoleh nilai 59,60 dan termasuk kategori cukup baik. Sedangkan hasil belajar IPS Siswa Kelas V SD Negeri 104333 Marubun masuk dalam kategori baik, karena nilai hasil belajar siswa adalah 75,93 dan termaksud kategori baik. Untuk uji kolerasi diperoleh nilai t adalah 4,942 sedangkan t dalam tabel adalah 2,05 sehingga t hitung lebih besar dari t dalam tabel maka ada hubungan yang signifikan antara antara kecerdasan emosional terhadap hasil belajar IPS siswa kelas V SD Negeri 104333 Marubun Tahun Ajaran 2021/2022.Kata Kunci: Emotional Intelligence and Social Studies Learning Outcomes